An IL-17A-centric response to Epstein-Barr virus DNA mediated by dendritic Cell-T cell interactions - Shehab, Marwa; Hussein, Hadi; Fadlallah, Sukayna; Rahal, Elias A. (Frontiers in Molecular Biosciences, 2024)
The Epstein-Barr virus has been associated with a considerable number of autoimmune diseases. We have previously demonstrated that EBV DNA enhances the production of IL-17A, a pro-inflammatory cytokine, via endosomal Toll-like receptor signalling. Hence, we used RNA-seq to analyze the transcriptional profile of mouse immune cells treated with EBV DNA. We observed that EBV DNA upregulates an IL-17A-centric network of mediators. Ensemble Gene Set Enrichment Analysis (EGSEA) showed enriched expression of sets involved in inflammatory responses including IFNγ and TNF-α-associated pathways as well as proinflammatory diseases. On the other hand, while macrophages and B cells were somewhat able to induce an IL-17A response from T cells to EBV DNA, they were less potent than dendritic cells. EBV virions were also capable of eliciting the production of inflammatory mediators from dendritic cell-T cell cultures largely mirroring responses to the viral DNA. Given the wide prevalence of EBV in the population, our analyses reveal a network of mediators and cell types that may serve as therapeutic targets in a large proportion of people affected by autoimmune diseases.